2021
DOI: 10.1016/j.lungcan.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Care disruptions among patients with lung cancer: A COVID-19 and cancer outcomes study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
12
1
1
Order By: Relevance
“…While other studies have reported delayed/disrupted cancer screening and care during COVID [ 12 14 ], our study of real-world adult patients with MM in the US shows little evidence of delayed diagnosis or worsening of clinical presentation, and only modest changes in treatment early during the pandemic. One explanation for this difference is that clinical MM presentation often involves kidney failure, anemia, hypercalcemia, and pathologic bone fractures that must be addressed urgently.…”
Section: To the Editorcontrasting
confidence: 56%
“…While other studies have reported delayed/disrupted cancer screening and care during COVID [ 12 14 ], our study of real-world adult patients with MM in the US shows little evidence of delayed diagnosis or worsening of clinical presentation, and only modest changes in treatment early during the pandemic. One explanation for this difference is that clinical MM presentation often involves kidney failure, anemia, hypercalcemia, and pathologic bone fractures that must be addressed urgently.…”
Section: To the Editorcontrasting
confidence: 56%
“…By comparison, 1.8% (2/111) of patients treated with pembrolizumab on or after March 11, 2020, in the current study developed SARS-CoV-2 infection. Early on in the pandemic, BC Cancer proactively implemented strategies to reduce the risk of virus transmission amongst patients and healthcare workers (BC Cancer 2020 ). Key components of this policy (aside from a shift to virtual consultation and follow-up assessments) included: use of personal protective equipment, screening patients (both the day before and the day of their cancer clinic appointment) for symptoms of COVID-19 disease, and restricting building access to healthcare providers and patients.…”
Section: Discussionmentioning
confidence: 99%
“…British Columbia (BC) Cancer provides publicly funded oncologic care for the 5.2 million residents of the province of British Columbia, Canada. At the onset of the pandemic, BC Cancer issued clinical management guidelines to limit COVID-19 dissemination amongst patients with cancer and to prioritize healthcare services (BC Cancer 2020 ). For example, in-person appointments were deferred in favor of telemedicine (defined as the delivery of health care services using communication technologies where distance is a critical factor) and extended interval immunotherapy dosing became available (Pan American Health Organization 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2021) 11 Spain April 24, 2020–July 3, 2020 447 281/447 (62.9%) 146/447 (32.7%) Sheena et al. (2021) 12 USA March 2, 2020–March 6, 2020 13/313 (4.2%) Not applicable Not applicable Lei et al. (2020) 13 People’s Republic of China January 3, 2020–May 6, 2020 50/11,660 (0.4%) 12/45 (26.7%) 11/45 (24.4%) Liang et al.…”
mentioning
confidence: 99%
“…Any accompanied respiratory disease including COVID-19 may inevitably deteriorate and impact patients’ subsequent treatment and prognosis. Several previous studies 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 investigated the impact of COVID-19 in patients with lung cancer, revealing that lung cancer may worsen the degree of COVID-19, leading to higher incidence of severe COVID-19. Meanwhile, patients with lung cancer accompanied by COVID-19 may suffer from higher mortality rate in a relatively short period of time, suggesting the underlying damaging interaction between lung cancer and COVID-19 ( Table 1 ).…”
mentioning
confidence: 99%